Duane Michals (1939-1997) (Checkerboard Foundation, 1978)
A film poem evoking the spirit of Duane Michals' photographic sequences and his series of still photographs which tell fantastic and dreamlike stories. Stresses the surrealism and humor in his work, extending them through parallel filmic techniques and using Michals' own voice-over narration.